(untitled) (Global Journal of Management and Business Research, 2017)
Considering the employees as valuable asset and investing on them goes a long way to the success of an organization. In this era of stiff competition, employers look for the best talent available, meaning they want to have the people having best things on them. A good image as an employer can stir the rate of recruiting large pool of candidates, like branding attracts consumers in marketing. This employment branding can attract and retain top class employees while ensuring organizational growth. Organizations need to think from vision and mission in order to align its activities with total branding experience. Internal and external branding is of equal importance which can be promoted in a number of ways. Some very easy practices like giving fair benefits, recognizing employee contributions, creating a culture of mutual trust may prove worthy. At the same time organizations need to express their philosophies and practices of this culture to the society they operate in. simple, yet effective channel can be seminars, usage of theme statement highlighting care for employees, participating in job fairs, sponsoring relevant events etc. A company having good consumer branding and employment branding can only expect to achieve its vision.